Nutritional Value, Fermentation Characteristics and In Vitro Degradability of Whole Wheat Hay Harvested at Three Stages of Maturity - Xiaochen Lang; Meng Yang; Atef M. Saleem; Xiaojing Zhao; Hua Xu; Yan Li; Ruiting Xu; Jiaqiu Cao; Congcong Xu; Yushan Cui; Jia Li; Jiahui Li; et al. (Animals, 2022)
The nutritional value of whole crop wheat hay (WCWH) harvested at different maturation stages are different, and its feeding effects on dairy cows have not been thoroughly evaluated. In this study, the in vitro digestibility of whole wheat (Nongda 22) hay harvested during the flowering, late milk and dough stages were evaluated using batch culture technique. The neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents of whole wheat hay decreased by 35.5% and 40.4%, respectively, whereas the non-fibrous carbohydrates (NFC) content increased by 50.3% in WCWH harvested during the dough stage as compared to the flowering stage (p < 0.01). The pH of the fermentation liquid and acetate to propionate ratio was greatest in the wheat harvested during the flowering stage and lowest during the dough stage (p = 0.03), whereas the volatile fatty acid (VFA) concentration was greatest during the dough stage and lowest during the flowering stage (p < 0.01). The dry matter loss (DML) was 9.6% and 6.2% greater (p < 0.01) during the late milk stage than in the flowering or dough stages, and the NDF loss (NDFL; p = 0.01) and ADF loss (ADFL; p < 0.01) was greater in both the flowering and late milk stages. In conclusion, though the content of NDF was lower in the dough stage, and the starch to NFC ratio was greater, we determined that the optimal harvest stage should be the late milk stage due to the greater dry matter digestibility, the relatively greater NFC content and the shorter planting days.